Investigation of the chemical composition and nutritional value of smoothhound shark (Mustelus mustelus) meat - Bosch, Adina Cornelia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2012.